1919 : la commune de Budapest - Bardy, Roland; Chaleil, Max (Paris : Editions de la Tête de Feuilles, 1972)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: communisme; Hongaarse Revolutie (1919); Hongarije; Boedapest